Association of the abbreviated burn severity index with mortality in severely burned patients: A meta-analysis - Guangrong Deng; Ling Tang; Qian Yang; Zhengyong Li (PLoS ONE, 2025)
Background and purpose The ability of the abbreviated burn severity index (ABSI) to predict death among patients with severe burns remains unclear. This meta-analysis aimed to identify the association between the ABSI and mortality in severely burned patients. Methods The PubMed, EMBASE and Web of Science databases were searched up to September 15, 2024. The odds ratios (ORs) with 95% confidence intervals (CIs) were combined, and a subgroup analysis was conducted on the basis of age, ABSI grouping method and OR source. All the statistical analyses were performed with STATA version 15.0. Results Sixteen studies with 4011 cases were included in the analysis. The pooled results demonstrated that an elevated ABSI was significantly related to an increased risk of mortality (OR = 1.72, 95% CI: 1.48–2.00; P < 0.001). In addition, subgroup analysis by age (adult: OR = 1.35, P < 0.001; child: OR = 68.40, P < 0.001), ABSI grouping method (dichotomous: OR = 16.14, P < 0.001; continuous: OR = 1.59, P < 0.001) and OR source (univariate: OR = 11.42, P = 0.015; multivariate: OR = 1.51, P < 0.001) yielded similar results. Conclusion The ABSI serves as a reliable prognostic indicator in severely burned patients, and patients with an elevated ABSI are at increased risk of death.